2010
DOI: 10.5014/ajot.2010.08073
|View full text |Cite
|
Sign up to set email alerts
|

Use of Occupations and Activities in a Modified Constraint-Induced Movement Therapy Program: A Musician’s Triumphs Over Chronic Hemiparesis From Stroke

Abstract: OBJECTIVE. This case report addresses the use of therapeutic occupations and activities within a modified constraint-induced movement therapy (mCIMT) approach for a 52-yr-old female violinist 4 yr after ischemic stroke. METHOD. Analysis of occupational performance was completed before and after intervention using a modified version of the Fugl-Meyer Sensorimotor Evaluation, the Motor Functioning Assessment, the Arm Improvement and Movement Checklist, and information obtained from a client journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…2007). When a typical modified constraint‐induced movement therapy programme was used for a 52‐year‐old female violinist with upper extremity motor control impairments after ischaemic stroke, improved function (upper extremity muscle strength, grips strength, pinch strength) in the affected extremity was noted (Earley et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2007). When a typical modified constraint‐induced movement therapy programme was used for a 52‐year‐old female violinist with upper extremity motor control impairments after ischaemic stroke, improved function (upper extremity muscle strength, grips strength, pinch strength) in the affected extremity was noted (Earley et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, these results also showed the opposed results with the report that shows a significant improvement in balance of body and muscle strength of leg when movement/exercise programme was applied for eight weeks to the elderly with cognitive impairments and another research that reports the significant improvement in the balance of body and muscle strength of leg and muscle flexibility after 16 weeks. However, most studies showed significant improvements in hip joint flexion, muscle strength and ADLs (Lim 2002, Earley et al. 2010, Guidetti et al.…”
Section: Discussionmentioning
confidence: 99%
“…The populations studied reflect the predominance of heart disease as a leading chronic condition in the United States (Go et al, 2013). Of the 42 studies reviewed, 22 (52%) involved the stroke population (Beckelhimer, Dalton, Richter, Hermann, & Page, 2011;Earley, Herlache, & Skelton, the area of neurorehabilitation were studied over the past 5 yr. See Tables 2 and 3, which summarize the interventions studied and the size of populations involved. The broad categories under which most of these interventions can be subdivided are as follows: high technology, low technology, established methods, occupation-centered approaches, and cognitive-based approaches.…”
Section: Populations Studiedmentioning
confidence: 99%
“…Another high-technology intervention studied over the same period included the Interactive Metronome; the authors sought to determine the effect on UE hemiplegic arm function after stroke (Beckelhimer et al, 2011). Electrical stimulation (ES) was the central topic for 3 of the hightechnology articles: ES was combined with bracing to reduce hemiplegic arm spasticity (Hardy et al, 2010), was embedded in a UE orthosis used to improve arm function after stroke , and was part of a grasp-release training program for people with tetraplegia (Martin et al, 2012). Virtual reality was used to assess multitasking of patients poststroke through virtual grocery shopping (Rand et al, 2009), and telehealth strategies were prominent in 2 studies: 1 to manage fatigue levels in patients with multiple sclerosis (Finlayson et al, 2012) and 1 to facilitate home training in the use of the electrical stimulation orthotic mentioned previously .…”
Section: Populations Studiedmentioning
confidence: 99%
“…Since appearing in those "first in class" papers, the term "modified constraint-induced therapy" and its abbreviation (mCIT) have consistently referred to a specific, 10-week, protocol as described herein. Nonetheless, the term "modified constraint-induced therapy" and its abbreviation have recently been attributed to any protocol in which the parameters of CIT were modulated e.g., (Earley et al, 2010;Aarts et al, 2011;Leung et al, 2009). Such work can create confusion, since later authors are claiming to test mCIT, yet their treatment regimens are entirely different than the original mCIT work (Kaplon et al, 2007;Page et al, 2005Page et al, , 2002bPage et al, , 2001Page et al, , 2002cPage et al, , 2004Page et al, , 2008Page and Levine, 2003) in at least two key ways: (a) their protocols do not match the 10-week mCIT duration parameters that were developed to overcome the intensive CIT limitations; and/or (b) the protocols do not contain many of the behavioral elements that differentiate mCIT from other treatment regimens.…”
Section: Making Soup or Just Boiling Water? The Current Papermentioning
confidence: 99%